2014
DOI: 10.3233/bme-141191
|View full text |Cite
|
Sign up to set email alerts
|

Working memory training using EEG neurofeedback in normal young adults

Abstract: Recent studies have shown that working memory (WM) performance can be improved by intensive and adaptive computerized training. Here, we explored the WM training effect using Electroencephalography (EEG) neurofeedback (NF) in normal young adults. In the first study, we identified the EEG features related to WM in normal young adults. The receiver operating characteristic (ROC) curve showed that the power ratio of the theta-to-alpha rhythms in the anterior-parietal region, accurately classified a high percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Here, the specificity of NFB control could be tested on both the spatial and temporal dimensions of feedback signals, which might include brain regions predefined via inverse-source localization (Congedo et al, 2004 ) or rhythms that need to be controlled for a particular temporal duration/dynamic (Congedo et al, 2004 ; Hoedlmoser et al, 2008 ). In this regard, future NFB studies could also take inspiration from recent BCI approaches which have exploited machine-learning methods (Lotte et al, 2007 ) for identifying the individual-specific EEG patterns for training, and that may be based on a priori behavioral performance (Xiong et al, 2014 ).…”
Section: Neurofeedback: Unlocking Direct Control Of Brain Oscillationmentioning
confidence: 99%
“…Here, the specificity of NFB control could be tested on both the spatial and temporal dimensions of feedback signals, which might include brain regions predefined via inverse-source localization (Congedo et al, 2004 ) or rhythms that need to be controlled for a particular temporal duration/dynamic (Congedo et al, 2004 ; Hoedlmoser et al, 2008 ). In this regard, future NFB studies could also take inspiration from recent BCI approaches which have exploited machine-learning methods (Lotte et al, 2007 ) for identifying the individual-specific EEG patterns for training, and that may be based on a priori behavioral performance (Xiong et al, 2014 ).…”
Section: Neurofeedback: Unlocking Direct Control Of Brain Oscillationmentioning
confidence: 99%
“…Thirdly, the number of sessions used in NFT varies widely in the literature, and is usually dependent on the trained population as well as the specific protocol that is used (for a review see Enriquez-Geppert et al 2017 ). Reiner et al (2014) found posterior theta to change already after one session, followed by some studies that observed clear changes in alpha after only one neurofeedback training (Escolano et al 2014 ; Ros et al 2014 ; Xiong et al 2014 ). Also, Enriquez-Geppert et al ( 2014 ) found frontal-midline theta to change after eight sessions of NFT, making it difficult to explain the absence of changes in theta after 14 training sessions in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature and our own results [41], parietal alpha rhythm easy to isolate (in contrast to the sensorimotor rhythm, for example) and is easy to train with NFB practically in all subjects. Moreover, NFB that is based on the parietal alpha rhythms has been suggested as the approach to gaining a range of functional improvements, including improvements in cognition [61], [1], [19], attention [4], [39], [40], [8], working memory [11], [67], mood [42], [13], [43], and relaxation [5].…”
Section: Introductionmentioning
confidence: 99%